Traffic-aware contact plan design for disruption-tolerant space sensor networks - Fraire, Juan Andres (2016)
Delay and disruption tolerant networks (DTNs) are becoming an appealing solution for extending Internet boundaries across challenged network environments. In particular, if node mobility can be predicted as in space sensor networks (SSNs), routing schemes can take advantage of the a-priori knowledge of a contact plan comprising forthcoming communication opportunities. However, the design of such a plan needs to consider available spacecraft resources whose utilization can be optimized by exploiting the expected data which is largely foreseeable in typical Earth observation missions. In this work, we propose Traffic-Aware Contact Plan (TACP): a novel contact plan design procedure based on a Mixed Integer Linear Programming (MILP) formulation which exploits SSNs predictable properties in favor of delivering efficient and implementable contact plans for spaceborne DTNs. Finally, we analyze a low orbit SSN case study where TACP outperforms existing mechanisms and proves to be of significant impact on enhancing the delivery of sensed data from future space networks.